2012
DOI: 10.1111/j.1365-313x.2012.05024.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis SMALL AUXIN UP RNA63 promotes hypocotyl and stamen filament elongation

Abstract: SUMMARYAuxin regulates plant growth and development in part by activating gene expression. Arabidopsis thaliana SMALL AUXIN UP RNAs (SAURs) are a family of early auxin-responsive genes with unknown functionality. Here, we show that transgenic plant lines expressing artificial microRNA constructs (aMIR-SAUR-A or -B) that target a SAUR subfamily (SAUR61-SAUR68 and SAUR75) had slightly reduced hypocotyl and stamen filament elongation. In contrast, transgenic plants expressing SAUR63:GFP or SAUR63:GUS fusions had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
222
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(257 citation statements)
references
References 65 publications
16
222
0
3
Order By: Relevance
“…8 We found that SAUR41 displayed distinctive expression patterns in Arabidopsis roots; it was normally restricted to the quiescent center and cortex/endodermis initials of primary root meristems. 9 During lateral root development, SAUR41 was also expressed in prospective stem cell niches of lateral root primordial and in expanding endodermal cells surrounding the lateral root primordia.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…8 We found that SAUR41 displayed distinctive expression patterns in Arabidopsis roots; it was normally restricted to the quiescent center and cortex/endodermis initials of primary root meristems. 9 During lateral root development, SAUR41 was also expressed in prospective stem cell niches of lateral root primordial and in expanding endodermal cells surrounding the lateral root primordia.…”
mentioning
confidence: 75%
“…9 In the meantime, SAUR36, another clade III SAUR gene of Arabidopsis has been identified as a positive regulator of leaf senescence and a negative regulator of leaf size. 10 In an independent study, SAUR63 localized primarily to the plasma membrane, 7,8 whereas SAUR36 targeted the nucleus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ectopic expression of several SAUR family genes resulted in elongated hypocotyls in the light and that plants overexpressing SAUR19 exhibited opened cotyledons in the dark (23)(24)(25). However, several other SAURs have been suggested to inhibit cell expansion in certain organs (26)(27)(28).…”
Section: Saur Family Genes Exhibit Remarkably Organ-specific Light-mentioning
confidence: 99%
“…Based on microarray analysis, about half of SAURs are up-regulated by auxin treatment in Arabidopsis (22). Overexpression of several distinct SAUR genes resulted in increased growth of cotyledons, hypocotyls, or roots, respectively (23)(24)(25), whereas a few SAURs have been suggested to negatively regulate cell growth in specific organs (26)(27)(28). Recently, it has been found that SAURs could interact with D-clade type 2C protein phosphatase (PP2C) proteins to inhibit their phosphatase activities, therefore activating…”
mentioning
confidence: 99%